Accountability for performance in English and Scottish fire and rescue services from 2010 to 2016. Issue 1 (2nd January 2021) - Taylor, Lynda; Greenhalgh, Kirsten; Murphy, Peter
ABSTRACT: Using evidence from English and Scottish fire and rescue services from 2010 to 2016, this paper shows how divergent performance management regimes can affect public accountability. Performance management regimes enable agencies and the public to hold public sector organizations accountable by facilitating evaluation of their accomplishments. However, local as opposed to central, control over performance management can have quite different implications for public accountability. IMPACT: The findings reported in this paper will encourage public sector policy-makers and managers to reflect upon how far particular performance management regimes enable them to facilitate improved accountability to the communities they serve. On one hand, localism policies can lead to deficits in accountability. On the other, policies that focus on centralized targets and independent scrutiny can deliver stronger accountability while maintaining local responsiveness.